Physicochemical and gelling properties of whey protein hydrolysates generated at 5 and 50 °C using Alcalase® and Neutrase®, effect of total solids and incubation time. (November 2020) - Dermiki, Maria; FitzGerald, Richard J.
Abstract: Gelation temperature (Tg ), apparent viscosity (ηapp ), turbidity and chromatography profiles of whey protein concentrate (WPC) and corresponding hydrolysates (WPHs) generated with Alcalase® and Neutrase® at different temperatures and total solids (TS) were compared. WPC incubated with Alcalase at 50 °C exhibited the highest rate and degree of hydrolysis (DH). After 4 h, the 5 °C Alcalase WPH (10% TS) had a DH and molecular mass distribution similar to those generated at 5 and 50 °C with Neutrase; however, the chromatography profiles differed. Tg was lower for WPHs than for WPC and depended on both the enzyme and TS. Moreover, the Tg s were lower for the Alcalase hydrolysates than for those generated with Neutrase. The ηapp and turbidity properties of the hydrolysates depended on the enzyme used, solution TS and incubation temperature. Hydrolysates had lower ηapp than WPC. The 50 °C Neutrase hydrolysates displayed lower turbidity than the corresponding Alcalase hydrolysates.